Comparison of insulin intensification strategies with insulin lispro low mixture twice daily versus basal insulin glargine and prandial insulin lispro once daily in East Asian and Caucasian patients with type 2 diabetes mellitus†: 在东亚与白种2型糖尿病患者中每日两次低预混赖脯胰岛素与每日一次基础甘精胰岛素联合餐时赖脯胰岛素这两种胰岛素强化治疗方案的对照研究. (12th July 2016) - Jeong, In‐Kyung; Chung, Choon Hee; Zhou, Zhiguang; Han, Jeong Hee; Duan, Ran; Edralin, Diana M.; Rodriguez, Angel
Abstract: Background: This analysis evaluated efficacy and safety of insulin lispro low mixture (LM25) twice daily (breakfast and dinner) versus basal insulin glargine (bedtime) plus prandial insulin lispro (IGL) once daily before the largest meal in East Asian (EA) and Caucasian patients with type 2 diabetes mellitus who failed to reach glycemic targets on basal insulin glargine with metformin and/or pioglitazone. Methods: Included patients had an HbA1c ≥7.5% and ≤10.5% and fasting plasma glucose ≤6.7 mmol/L. Primary outcome was HbA1c change at 24 weeks. Results: Baseline mean HbA1c was numerically similar between groups in EA (n = 79) and Caucasian (n = 278) patients. Mean (± SD) HbA1c decreased significantly from baseline to 24 weeks for LM25 and IGL in both subpopulations (EA: –1.32 ± 0.96% and –0.89 ± 0.96%; Caucasian: –1.24 ± 0.98% and –1.04 ± 0.97; all P < 0.0001). The respective proportions reaching HbA1c ≤7.0% at Week 24 in the LM25 and IGL groups were 33.3% and 22.9% (EA) and 37.2% and 34.1% (Caucasian). Mean (± SD) rates of hypoglycemia per 30 days in the LM25 and IGL groups were 0.74 ± 1.16 and 1.22 ± 1.36 (EA) and 1.38 ± 2.04 and 1.65 ± 2.43 (Caucasian). Mean (± SD) weight gain changes in the LM25 and IGL groups were 0.62 ± 2.78 and 0.51 ± 2.63 kg (EA) and 1.77 ± 2.91 and 0.67 ± 3.09 kg (Caucasian). Conclusions: Both strategies improved glycemic control in a small group of EA and Caucasian patients not adequately controlled on insulin glargine plus metformin and/or pioglitazone. Abstract : Summary of key efficacy measures and reported hypoglycemia in East Asian and Caucasian patients with type 2 diabetes mellitus treated with insulin lispro low mixture (LM25) or insulin glargine plus prandial insulin lispro (IGL).